Continuous surface treatment for aluminum alloy sheet coils

A fluorine-free continuous coil surface treatment method for aluminum alloy sheets addresses environmental concerns and adaptability issues by using a Ti/Zr conversion process, ensuring smooth and corrosion-resistant surfaces for both 5XXX and 6XXX alloys without process changes.

JP7621258B2Active Publication Date: 2025-01-24CONSTELLIUM NEUF BRISACH SAS +1
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
JP2021541574
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-01-18
Filing Date
2020-01-17
Publication Date
2025-01-24
Estimated Expiration
2040-01-17

AI Technical Summary

Technical Problem

Existing surface treatment methods for aluminum alloy sheets in the automotive industry are environmentally unfriendly due to the use of fluorine-containing baths, require multiple steps, and are not adaptable for both 5XXX and 6XXX alloys without process modifications, posing health and environmental risks and increasing costs.

Method used

A continuous coil surface treatment method using a fluorine-free acidic solution for etching followed by a conversion solution with a specific Ti/Zr ratio, applied in a continuous process suitable for both 5XXX and 6XXX alloys, eliminating the need for process changes and ensuring smooth, corrosion-resistant surfaces.

Benefits of technology

The method provides environmentally friendly, efficient, and cost-effective surface treatment for both 5XXX and 6XXX alloys, achieving smoother surfaces and consistent Ti/Zr ratios without the need for process modifications, reducing health and environmental risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621258000002
    Figure 0007621258000002
  • Figure 0007621258000003
    Figure 0007621258000003
  • Figure 0007621258000001
    Figure 0007621258000001
Patent Text Reader

Abstract

The present invention relates to a continuous coil surface treatment method suitable for coils of both 5XXX and 6XXX aluminum alloy sheet. The method includes the sequential steps of etching the surface with a fluorine-free acid solution, rinsing with deionized water, applying a conversion solution containing titanium and zirconium, and drying. The surface treatment method of the present invention is environmentally friendly and allows for the efficient and reliable production of treated surfaces for both 5XXX and 6XXX alloys. It is particularly suitable for the production of aluminum alloy sheet for the automotive industry.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of continuous surface treatment of aluminum alloy sheets and strips and parts stamped from these sheets, in particular 5XXX or 6XXX type alloys according to the Aluminum Association for the manufacture of body parts for motor vehicles. [Background technology]

[0002] Aluminum is increasingly being used in automobile manufacturing to reduce the weight of the vehicle and therefore fuel consumption and the emission of pollutants and greenhouse gases. Sheets are used to manufacture body exterior parts, especially hoods and doors and structural parts. This type of application requires a set of properties: mechanical strength, corrosion resistance and formability, which are sometimes in conflict with an acceptable cost for mass production.

[0003] For automotive parts, preparation of surfaces adapted for assembly operations, especially adhesive bonding and welding, may be required. These pretreatments are time-consuming and costly, especially because the immersion liquids are corrosive and require special health and environmental considerations. Recent treatments do not contain chromium for environmental reasons, but use elements such as organophosphorus, silanes and derivatives, titanium and / or zirconium. For example, such treatments are described in patents and patent applications such as US 5514211, US 5879437, US 6167609, US 2013 / 284049, US 2011 / 041957, US 2016 / 319440.

[0004] French patent no. 2 856 079 describes an alternative process which is simplified by using an atmospheric plasma.

[0005] US Patent No. 5,868,872 discloses a chrome-free no-rinse process, particularly for applications in the food packaging industry. The patent does not disclose an etching step prior to treatment, only an acidic or alkaline cleaner.

[0006] US Patent No. 6,562,148 discloses a method for pre-treating a workpiece having an aluminum or aluminum alloy surface, comprising the steps of rinsing with an acidic aqueous solution containing a mineral acid, rinsing with water, and contacting with an acidic aqueous solution containing Ti and Zr as fluoride complexes in a Ti:Zr weight ratio of 2:1 to 1:2, and which is free of chromium and polymers.

[0007] European Patent Application Publication No. 2537674 discloses an aluminum or aluminum alloy having a surface treatment coating film on the surface of a substrate formed from aluminum or an aluminum alloy, the surface treatment coating film having the ability to maintain hydrophilicity, high corrosion resistance, antibacterial properties and deodorizing properties for a long period of time.

[0008] The surface preparation is usually carried out using a continuous coil surface treatment line which allows for the surface treatment of sheet coils.

[0009] The surface treatment line may include continuous solution annealing and hardening or may be a line dedicated to surface treatment. Several surface treatment steps are applied to progressively modify the surface properties to suit the product's application in the automotive sector by optimizing the weight of the chemical layer. The first surface treatment step is usually a sheet degreasing step used to remove oil residues on the sheet, present after the final rolling step. After the rolling process, the surface of the aluminum contains "altered areas", also called "altered layer" or "altered surface layer", and etching is used in the second surface treatment step to remove oxide layers and disturbed areas to ensure a uniform surface, which is more favorable for depositing products such as Ti / Zr conversion layers and for further corrosion / adhesion durability properties. The third surface treatment step is conversion coating, the purpose of which is to deposit precisely the weight of a layer (for example made of Ti and / or Zr) that promotes adhesion and corrosion resistance. It is generally accepted that the use of fluorine in the second etching process is necessary to remove "disturbed areas" and obtain a favorable surface for depositing the conversion layer. However, the use of fluorine-containing baths poses special health and environmental considerations. Another requirement is that surface treatment lines dedicated to automotive applications must be able to process alternating coils of 5XXX and 6XXX alloy sheet. It is therefore economically advantageous to maintain the same process for the different types of alloys. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] U.S. Pat. No. 5,514,211 [Patent Document 2] U.S. Pat. No. 5,879,437 [Patent Document 3] U.S. Patent No. 6,167,609 [Patent Document 4] US Patent Application Publication No. 2013 / 284049 [Patent Document 5] US Patent Application Publication No. 2011 / 041957 [Patent Document 6] US Patent Application Publication No. 2016 / 319440 [Patent Document 7] French Patent No. 2856079 [Patent Document 8] U.S. Pat. No. 5,868,872 [Patent Document 9] U.S. Patent No. 6,562,148 [Patent Document 10] European Patent Application Publication No. 2537674 Summary of the Invention [Problem to be solved by the invention]

[0011] It is an object of the present invention to develop an improved, more environmentally friendly surface treatment method for producing treated surfaces in an efficient and reliable manner that provides treated surfaces for both 5XXX and 6XXX alloys. [Means for solving the problem]

[0012] The subject of the invention is a continuous coil surface treatment method suitable for both coils of 5XXX and 6XXX aluminum alloy sheets having a surface, a) optionally cleaning the surface of the aluminum alloy sheet; b) etching the surface of the optionally cleaned aluminum alloy sheet with a fluorine-free acidic solution; c) rinsing the surface of the etched aluminum alloy sheet with deionized water; d) applying to the surface of the etched aluminum alloy sheet a conversion solution comprising titanium and zirconium in a zirconium to titanium weight ratio of about 3.0 to about 5.0, preferably 3.2 to 4.0; e) optionally rinsing the surface of the converted aluminum alloy sheet with deionized water; f) drying the surface of the aluminum alloy sheet The method includes the following successive steps: [Brief description of the drawings]

[0013] [Figure 1a] 1 is an SEM micrograph of a 6016 surface etched with a fluorine-containing etching solution. [Figure 1b] 1 is an SEM micrograph of a 6016 surface etched with a fluorine-free etching solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] All aluminum alloys referred to below are designated using the conventions and designations defined in the Register Record Series periodically published by the Aluminum Association, unless otherwise noted.

[0015] Unless otherwise specified, the definitions in the EN12258 standard apply.

[0016] The method of the present invention is a continuous coil surface treatment method that is suitable for coils of both 5XXX and 6XXX alloy sheet. One significant advantage of the present invention is that there is no need to change or modify the process when switching a line from a 5XXX to a 6XXX alloy.

[0017] The method is suitable for the treatment of coils of 5XXX alloy sheet and for the treatment of coils of 6XXX alloy sheet, preferably the coils are coils of sheet made from an aluminium alloy selected from the group consisting of AA5754, AA5182, AA6451, AA6605, AA6005, AA6005A, AA6016, AA6116, AA6022, AA6013, AA6056, AA6156, AA6111 and AA6014.

[0018] In the first step, the sheet surface may be optionally cleaned. Cleaning may be used to remove residual oils left by the rolling process. Optionally, cleaning can be performed by hot water spray, and / or by using organic solvents, and / or by using detergents and / or surfactants, such as alkaline detergents. For some continuous processing lines, the sheet may be sufficiently degreased by a prior heat treatment, and a cleaning step may not be necessary. Similarly, in some cases, cleaning and etching may be performed simultaneously to simplify the process. For productivity and cost reasons, it is usually preferable to avoid the presence of a cleaning step.

[0019] In a next step, the surface of the optionally cleaned aluminum alloy sheet is etched with a fluorine-free acid solution. The inventors have discovered that by combining a fluorine-free acid solution with a conversion bath containing Ti and Zr in certain quantities, it is possible to treat 5XXX and 6XXX sheets in the same bath and obtain a satisfactory conversion. Preferably, the etching with the fluorine-free acid solution is performed chemically, not electrochemically.

[0020] Preferably, the fluorine-free acid solution comprises sulfuric acid, nitric acid, phosphoric acid, or a mixture thereof. Advantageously, the fluorine-free acid solution comprises at least 80% sulfuric acid and phosphoric acid, or a mixture thereof. In one embodiment, the fluorine-free acid solution does not contain nitric acid. When an acid mixture is used, it is advantageous that this mixture comprises at least 80% sulfuric acid. Advantageously, the sulfuric acid concentration of the fluorine-free acid solution is from about 2 g / l to about 60 g / l, preferably from 15 g / l to 50 g / l. Optionally, the fluorine-free acid solution may comprise one or more additives (e.g. surfactants and / or detergents) and / or one or more accelerators. The surfactants and / or detergent additives may be included in the fluorine-free acid solution at a concentration within the range of about 0.05% to 3% by weight. Preferably, the surfactant and / or detergent additive may be included in the fluorine-free acidic solution at a concentration within the range of about 0.1% to 2.5% by weight, about 0.2% to 2% by weight, about 0.3% to 1.5% by weight, or about 0.4% to 1.3% by weight. A suitable accelerator that may be included in the fluorine-free acidic solution includes ferric sulfate. The accelerator may be included in the fluorine-free acidic solution at a concentration within the range of about 0.005% to 0.4% by weight. For example, the accelerator may be included in the fluorine-free acidic solution at a concentration within the range of about 0.01% to 0.3% by weight, about 0.03% to 0.2% by weight.

[0021] The fluorine-free acid solution may be heated to a temperature of about 55° C. to about 85° C. The fluorine-free acid solution may be controlled within a roughly determined temperature and concentration range, for example, using a heat exchanger and a metering pump and a drain, and may be replaced or replenished in a suitable manner.

[0022] The fluorine-free acid solution may be applied by spraying the solution onto the sheet or by immersing the sheet in a bath. Preferably, the fluorine-free acid solution is applied by immersion. Optionally, the fluorine-free acid solution may be circulated to ensure continuous exposure of fresh solution to the sheet surface. In an advantageous embodiment, the fluorine-free acid solution is continuously treated with an exchange resin in order to maintain a limited amount of Al and Mg ions in the solution. Preferably, the fluorine-free acid solution contains less than about 3 g / l aluminum and magnesium ions. Advantageously, the fluorine-free acid solution may contain less than 2 g / l aluminum and magnesium ions. The contact time for the acid etching step may be from about 5 seconds to about 30 seconds, or preferably from about 10 to about 20 seconds.

[0023] Advantageously, the etching removal is between 0.01 and 0.2 g / m for 6XXX alloys. 2 , preferably 0.01 to 0.1 g / m 2 , and 0.1 to 0.2 g / m for 5XXX alloys. 2 In the fluorine-free acid solution of the present invention, the etching removal is substantially lower than that known from the prior art fluorine-containing acid solutions. This is advantageous due to the limitation of Al and Mg ions in the solution. Likewise, the inventive etching provides an advantageously smoother surface compared to the prior art etching, in particular with less or even no pitting.

[0024] After etching, it is necessary to rinse the surface of the etched aluminum alloy sheet with deionized water. Preferably, the deionized water in this step has a conductivity of less than or equal to 50 μS / cm. The rinsing step is preferably carried out at a temperature in the range of about 37° C. to about 70° C. Advantageously, the rinsing step may be carried out at a temperature of about 40° C. to about 65° C., preferably about 45° C. to about 60° C. The rinsing may be a progressive cascading system. Preferably, spraying is used for the rinsing step.

[0025] The subsequent step is to apply a conversion solution containing titanium and zirconium to the surface of the etched aluminum alloy sheet in a zirconium to titanium weight ratio of about 3.0 to about 5.0, preferably 3.2 to 4.0. The inventors have discovered that by combining etching with a fluorine-free acidic solution and conversion with a conversion solution according to the present invention, it is possible to obtain a Zr / Ti weight ratio on the treated sheet surface of about 0.8 to about 1.3 for 5XXX and 6XXX alloys. This ratio is important for the adhesive bond properties of the sheet. One advantage of the present invention is that it is not necessary to modify the composition of the conversion solution to treat both 5XXX and 6XXX alloys. The conversion solution may be applied at a temperature of about 35°C to about 65°C. Preferably, the conversion solution is applied at different temperatures for 5XXX and 6XXX, typically at a temperature of about 40°C to about 50°C for 5XXX alloys and about 45°C to 55°C for 6XXX alloys. The conversion solution may be applied for a contact time of about 5 seconds to about 20 seconds. Preferably, the conversion solution is applied over different contact times for the 5XXX and 6XXX alloys, preferably for a contact time of about 5 seconds to about 9 seconds for the 5XXX alloys, typically for a contact time of about 7 seconds for the 5XXX alloys, and preferably for a contact time of about 8 seconds to about 12 seconds for the 6XXX alloys, typically for a contact time of about 10 seconds for the 6XXX alloys.

[0026] Preferably, the conversion solution contains titanium and zirconium, with a titanium content of about 20 to about 200 mg / l, preferably 60 to 140 mg / l. Advantageously, the conversion solution contains hexafluorotitanic acid, hexafluorozirconic acid, hydrofluoric acid and optionally ammonium monohydrogen difluoride. Additional fluoride (in the form of hydrofluoric acid and optionally ammonium monohydrogen difluoride) is advantageously added to complex the Al produced during treatment with the conversion solution. The pH of the conversion solution is advantageously adjusted upwards to a pH of about 2.5 to about 4.5, preferably 3.5 to 4, by adding an alkali such as ammonium hydroxide or ammonium monohydrogen difluoride. In an advantageous embodiment, the conversion solution is continuously treated with an exchange resin with the aim of maintaining a limited amount of Al and Mg ions in the solution. Preferably, the conversion solution contains less than about 80 ppm of aluminum and magnesium ions.

[0027] The conversion solution may be applied by spraying the solution onto the sheet or by immersing the sheet in a bath. Preferably, the conversion solution is applied by spraying the conversion solution onto the aluminum alloy sheet, preferably with at least five spray lamps. Applying the inventively described conversion solution by roll coating does not appear to be optimal, since the Ti / Zr ratio on the sheet will be the same as the Ti / Zr ratio in the conversion solution.

[0028] A subsequent step is optionally rinsing the surface of the converted aluminum alloy sheet with deionized water.

[0029] The final step is drying the surface of the aluminum alloy sheet. The drying step removes any moisture from the surface of the sheet. The drying step can be performed using an air dryer or an infrared dryer. The drying step can be performed for up to 5 minutes. The drying step can also be used for metallurgical purposes if necessary, especially for 6XXX alloys, whereby the coiling temperature is advantageously between 50°C and 120°C or preferably between 60°C and 100°C. EXAMPLES

[0030] The surfaces of aluminum alloy sheets were treated on a continuous line according to the method described herein. The sheets included 5182 aluminum alloy sheets and 6016 aluminum alloy sheets. The sheets were cleaned and etched by spraying with a sulfofluoride bath (8 g / l H2SO4, 0.4 g / l HF, 50°C) for tests 1 and 2, or a sulfuric acid bath (43 g / l H2SO4, 70°C) for tests 3-6. SEM micrographs of the surface obtained for the 6016 alloy etched with a sulfofluoride bath (test 2) and a micrograph of the surface obtained for the 6016 alloy etched with a sulfuric acid bath (test 6) are presented in Figures 1a and 1b, respectively. The inventive etch advantageously provides a smoother surface and much less pitting compared to the prior art etch. After etching, the sheets were rinsed with deionized water and treated by spraying with a Ti / Zr conversion treatment containing hexafluorotitanic acid, hexafluorozirconic acid, hydrofluoric acid, and ammonium difluoride at a pH of 3.8. The contact times, concentrations, and temperatures are shown in Table 1.

[0031] The amount of Zr and Ti deposited on the surface was measured by XRF at three locations across the width for six samples, and the average values ​​of the measurements are provided in Table 1.

[0032] [Table 1]

[0033] Conversion coating with bath C is according to the invention. By the method of the invention it is possible to obtain Zr / Ti ratios of 0.8 to 1.3 in a single bath for both 5XXX and 6XXX alloys and to obtain advantageous smoother surfaces.

Claims

1. 1. A continuous coil surface treatment process for treating alternating coils of 5xxx aluminum alloy sheet and 6xxx aluminum alloy sheet having a surface, comprising: b) etching the surface of the aluminum alloy sheet with a fluorine-free acidic solution; c) rinsing the surface of the etched aluminum alloy sheet with deionized water; d) applying to the surface of the etched aluminum alloy sheet a conversion solution comprising titanium and zirconium in a zirconium to titanium weight ratio of 3.0 to 5.0; f) drying the surface of the aluminum alloy sheet A method comprising the successive steps of: The method, wherein the conversion solution contains titanium and zirconium, and the titanium content is between 60 and 140 mg / l.

2. Before step (b), a) cleaning the surface of the aluminum alloy sheet; The method of claim 1 , comprising:

3. After step (d) and before step (f), e) rinsing the surface of the converted aluminum alloy sheet with deionized water. The method of claim 1 or 2, comprising:

4. The method of any one of claims 1 to 3, wherein the conversion solution comprises titanium and zirconium, with a zirconium to titanium weight ratio of 3.2 to 4.

0.

5. 5. The method of claim 1, wherein the conversion solution comprises hexafluorotitanic acid, hexafluorozirconic acid, hydrofluoric acid and optionally ammonium hydrogen difluoride.

6. 6. The method of claim 1, wherein the fluorine-free acidic solution comprises sulfuric acid, nitric acid, phosphoric acid, or a mixture thereof.

7. 7. The method according to claim 1, wherein the sulfuric acid concentration of the fluorine-free acidic solution is from 2 g / l to 60 g / l.

8. 7. The method according to claim 1, wherein the sulfuric acid concentration of the fluorine-free acidic solution is from 15 g / l to 50 g / l.

9. 9. The method of any one of claims 1 to 8, wherein the aluminium alloy sheet is manufactured from an aluminium alloy selected from the group consisting of AA5754, AA5182, AA6451, AA6005, AA6605, AA6005A, AA6016, AA6116, AA6022, AA6013, AA6056, AA6156, AA6111 and AA6014.

10. 10. The method according to any one of claims 1 to 9, wherein the applying in step (d) is carried out by immersing the aluminium alloy sheet in the conversion solution.

11. 10. The method according to any one of claims 1 to 9, wherein the applying in step (d) is carried out by spraying the conversion solution onto the aluminium alloy sheet.

12. 12. The method according to any one of claims 1 to 11, wherein the etching in step (b) is performed by spraying the aluminum alloy sheet with the fluorine-free acidic solution.

13. 13. The method according to any one of claims 1 to 12, wherein the fluorine-free acidic solution in step (b) contains less than 2 g / l of aluminum ions and magnesium ions.

14. 14. The method according to any one of claims 1 to 13, wherein the fluorine-free acidic solution contains a surfactant additive or accelerator and is used at a temperature of 55°C to 85°C for a period of 5 to 30 seconds.

Citation Information

Patent Citations

  • Aluminum or aluminum alloy material having surface treatment coating film, and surface treatment method therefor

    EP2537674A1

  • Surface treatment of aluminum alloy by preparation in a plasma atmosphere and treating in a metal salt bath using a no rinse technique, notably for motor vehicle fabrication operations

    FR2856079A1

  • Chromium-free process for rinseless treatment of aluminum and its alloys and solution suitable for the process

    JP1997511548A

  • Chromium-free surface treatment agent for metal, chromium-free surface treatment method for metal, and aluminum or aluminum alloy

    JP2003313678A

  • Chemical conversion liquid for metal structure and surface treatment method

    JP2010013677A